Sex‐ and gender‐associated clinical and psychosocial characteristics of patients with psoriasis. (18th May 2020) - Napolitano, M.; Mastroeni, S.; Fania, L.; Pallotta, S.; Fusari, R.; Uras, C.; Panebianco, A.; Cavani, A.; Sampogna, F.; Abeni, D.
Summary: Background: Sex and gender may affect disease prevalence, adverse effects and response to therapy. Aim: To analyse sex and gender differences in outpatients with psoriasis. Methods: A cross‐sectional study was conducted at IDI‐IRCCS, Rome, over a 3‐year period. In total, 3023 patients with psoriasis were enrolled. Anthropometric and demographic characteristics were recorded, and a dermatologist evaluated the clinical severity of disease. Quality of life (QoL) questionnaires were collected. Univariate and multivariate analyses were performed to examine factors associated with sex. Results: We found sex‐ and gender‐associated differences in clinical characteristics, disease severity, psychological distress and quality of life. Male sex was associated with body mass index, smoking, alcohol consumption, Psoriasis Area Severity Index ≥ 10 and age at onset ≥ 20 years. Female sex was associated with family history of diabetes, joint involvement, clinical type other than diffuse plaque psoriasis, higher psychological distress and a greater effect on QoL. Conclusion: Our study identified sex and gender differences of potential clinical relevance in psoriasis.